Flood Control Safety Situation of Main Stream Dikes in Xiangjiang River Basin - LIU Chang; PENG Lulu; YANG Liu; FENG Chang; ZHOU Jialong; LI Na; SHI Yabo (Renmin Zhujiang)
In order to clarify the evolution process and flood control situation of the main stream dikes in Xiangjiang River under different flood processes, a one-dimensional hydrodynamic model of the main stream of Xiangjiang River Basin was established by using the MIKE11 model, and the model was calibrated and verified by using the measured flood data. The evolution process of flood in the main stream of Xiangjiang River Basin was analyzed and calculated. The results show that in the calculated water level with a 20-year return period of the Zhuzhou–Jinggang section of the main stream of Xiangjiang River, the overflow-prone position on the left bank is more than that on the right bank, while in the calculated water level with 50-year and 100-year return periods, the overflow-prone position on the right bank is more than that on the left bank. Based on the analysis of the river sections at the stations, it is found that during the flood process with a 100-year return period, there are 48, 28, and 10 overflow-prone sections on both the left bank and right bank in Zhuzhou–Xiangtan section, Xiangtan–Changsha (III) section, and Changsha (III)–Jinggang section, respectively. The hydrodynamic model established in this paper can provide an effective reference for flood forecasting in the main stream of Xiangjiang River Basin in the future.